Study for the diagnostic screening of paroxysmal nocturnal hemoglobinuria in older patients with unexplained anemia and/or cytopenia - (:unkn) unknown (Verlag Klinisches Labor GmbH, 2020)
Background: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired hematopoietic stem cell disease that may lead to weakness and death of patients, if unrecognized and untreated. Although consensus guidelines were reviewed recently for the diagnostic screening of PNH with multi-parameter flow cytometry (FCM), until now, no study has investigated the efficiency of such clinical indications in older patients. Methods: Overall, 20 centers participated in the study and a total of 1,689 patients were included, 313 of whom were at geriatric age and 1,376 were aged 18 - 64 years. We evaluated the efficiency of consensus clinical indica-tions for PNH testing using FCM in peripheral blood samples and compared the results of older patients and pa-tients aged 18 - 64 years. Results: PNH clones were detected positive in 7/313 (2.2%) of the older patients. Five (74.4%) of the patients with PNH clones had aplastic anemia, 1 had unexplained cytopenia, and 1 patient had myelodysplastic syndrome (MDS) with refractory anemia. PNH clones were not detected in any older patients who were screened for unex-plained thrombosis, Coombs (-) hemolytic anemia, hemoglobinuria, and others (e.g., elevated lactate dehydroge-nase (LDH), splenomegaly). We detected PNH clones in 55/1376 (4%) samples of the patients aged under 65 years. Forty-two (76.4%) patients with PNH clones had aplastic anemia, 2 patients had Coombs (-) hemolytic anemia, 3 patients had unexplained cytopenia, 1 patient had MDS with refractory anemia, 1 patient had hemoglobinuria, and 6 (10.9%) had others (e.g., elevated LDH, splenomegaly). PNH clones were not detected in any patients who were screened for unexplained thrombosis. There was no statistical difference between the geriatric population and patients aged 18 - 64 years in terms of clinical indications for PNH screening with FCM (p = 0.49). Conclusions: Our results showed that the current clinical indications for PNH screening with FCM were also effi-cient in older patients. We suggest that older patients with unexplained anemia, myelodysplastic syndrome with refractory anemia, and unexplained cytopenia should be screened for PNH with FCM to identify patients who would benefit from treatment. © 2020 Verlag Klinisches Labor GmbH. All rights reserved.
Keywords: Consensus based clini-cal indications; Multiparameter flow cytometry; Older patients; Paroxysmal nocturnal hemoglobinuria